2023
DOI: 10.3390/v15081760
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines’ New Era-RNA Vaccine

Wenshuo Zhou,
Linglei Jiang,
Shimiao Liao
et al.

Abstract: RNA vaccines, including conventional messenger RNA (mRNA) vaccines, circular RNA (circRNA) vaccines, and self-amplifying RNA (saRNA) vaccines, have ushered in a promising future and revolutionized vaccine development. The success of mRNA vaccines in combating the COVID-19 pandemic caused by the SARS-CoV-2 virus that emerged in 2019 has highlighted the potential of RNA vaccines. These vaccines possess several advantages, such as high efficacy, adaptability, simplicity in antigen design, and the ability to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…This scenario opens the possibility for the selection of new traits, including drug resistance. Finally, the COVID-19 pandemic also boosted the development of mRNA vaccines [ 28 ]. Conventional mRNA vaccines are affordable and can be rapidly manufactured, displaying high flexibility and adaptability to address emerging variants and outbreaks [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario opens the possibility for the selection of new traits, including drug resistance. Finally, the COVID-19 pandemic also boosted the development of mRNA vaccines [ 28 ]. Conventional mRNA vaccines are affordable and can be rapidly manufactured, displaying high flexibility and adaptability to address emerging variants and outbreaks [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the COVID-19 pandemic also boosted the development of mRNA vaccines [ 28 ]. Conventional mRNA vaccines are affordable and can be rapidly manufactured, displaying high flexibility and adaptability to address emerging variants and outbreaks [ 28 ]. In fact, a study for an HCV mRNA vaccine candidate has already been reported by a north American group [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These antigens encode mRNA molecules inducing both humoral and cellular immunity, enabling immune cells to produce proteins from the virus. These proteins stimulate an immune response that forms a protective barrier against infection, aiding in pathogen recognition and destruction [ 23 ]. Since mRNA vaccines are not constructed by live pathogens, they are non-infectious and offer multiple advantages, such as high effectiveness, easy adaptability, an easy antigen design and the capacity to induce both humoral and cellular immunity.…”
Section: Research Progress Of the Tb Vaccinementioning
confidence: 99%
“…Among them, Zhou et al. reported that RNA vaccines possessed several advantages, such as high efficacy, adaptability, simplicity in antigen design, and the ability to induce both humoral and cellular immunity and that RNA vaccines could offer relatively rapid and cost-effective manufacturing, flexibility to target emerging or mutant pathogens and a potential approach for clearing immunotolerant microbes by targeting bacterial or parasitic survival mechanisms ( 78 ). However, mRNA vaccines had to be formulated in lipid nanoparticles for intramuscular injection, and the ionizable lipids, which are a necessary component of lipid nanoparticles for effective cell transport, have the potential to cause adverse events.…”
Section: Probiotics In the Post-covid-19 Eramentioning
confidence: 99%